2013
DOI: 10.1111/fcp.12032
|View full text |Cite
|
Sign up to set email alerts
|

No differences between men and women in adverse drug reactions related to psychotropic drugs: a survey from France, Italy and Spain

Abstract: A large number of studies have suggested that being a woman represents a potential risk factor for the development of adverse drug reactions (ADRs). The aim of this study is to further explore the differences between men and women with regard to reported ADRs, particularly those associated with psychotropic drugs. We used spontaneous reports of suspected ADRs collected by Midi-Pyr en ees (France), Veneto (Italy) and Castilla y Le on (Spain) Regional Pharmacovigilance Centres (January 2007-December 2009). All t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 35 publications
0
14
1
Order By: Relevance
“…28 We cannot provide any clear explanation for our noted sex differences in the reporting of ICSRs, which previously has been deemed as difficult to assess. 31 However, our finding of higher RR for serious ICSRs in men than in women is difficult to comprehend, especially when some studies imply that ADRs are more common in women. [8][9][10] The inevitable question arises: are reporters more likely to report serious ADRs for men compared to women?…”
Section: Icsrs Without Information On Sex Is Includedmentioning
confidence: 69%
See 2 more Smart Citations
“…28 We cannot provide any clear explanation for our noted sex differences in the reporting of ICSRs, which previously has been deemed as difficult to assess. 31 However, our finding of higher RR for serious ICSRs in men than in women is difficult to comprehend, especially when some studies imply that ADRs are more common in women. [8][9][10] The inevitable question arises: are reporters more likely to report serious ADRs for men compared to women?…”
Section: Icsrs Without Information On Sex Is Includedmentioning
confidence: 69%
“…20,[28][29][30] Stratification for seriousness is only performed in one of them. 30 Others have studied these issues based on a sample of selected drugs 19,31,32 or based on regional data. 16 None of them have investigated the impact of sex-dependent drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…conducted a prospective multicentre study and showed that females experienced 60% excess risk of ADR compared to males. However, the lack of a statistically significant difference was reported in the survey conducted in France, Italy and Spain . In 2015, Yu et al .…”
Section: Discussionmentioning
confidence: 97%
“…However, the lack of a statistically significant difference was reported in the survey conducted in France, Italy and Spain. 36 In 2015, Yu et al 37 conducted a systematic review to investigate variation of ADR in different genders across different medications and indicated the existence of gender differences in biological reactions to medication. This study also found ADR variation by gender across different medication agents, which more or less reflects gender differences in use or reaction pattern.…”
Section: Trends In Adr-related Hospitalisationsmentioning
confidence: 99%